Successful Selective Embolization for Recurrent Hemarthrosis after Knee Arthroplasty - Cristian Barrientos; Maximiliano Barahona; Tomas Cermenati; Rodrigo Wulf; Jaime Hinzpeter (Case Reports in Orthopedics)
Knee replacement has demonstrated to be a cost-effective treatment for severe knee osteoarthritis. Nevertheless, perioperative complications may occur, including recurrent hemarthrosis reaching an incidence between 0.3 and 1.6%. Success rate after conservative treatment has been reported to be above 80%, but in case of recurrence, computed tomography angiography, magnetic resonance angiography, and Doppler ultrasound have been used to conduct the diagnosis. Arthroscopy or selective embolization is used for treatment depending on the etiology of the bleeding. Open surgery is performed in the rare cases of failure of the above alternatives. The patient consulted seven months after total knee arthroplasty with sudden pain in the medial side of the knee. Infection was ruled out, and arthrocentesis shows hemarthrosis. Successful selective embolization of medial superior and lateral superior genicular artery was performed. After two years, the patients report 92 points in the Forgotten joint score, 0 in Womac pain, 1 in Womac stiffness, and 3 in Womac functional score.